2012
DOI: 10.1089/hum.2012.125
|View full text |Cite
|
Sign up to set email alerts
|

The Human Rhodopsin Kinase Promoter in an AAV5 Vector Confers Rod- and Cone-Specific Expression in the Primate Retina

Abstract: Adeno-associated virus (AAV) has proven an effective gene delivery vehicle for the treatment of retinal disease. Ongoing clinical trials using a serotype 2 AAV vector to express RPE65 in the retinal pigment epithelium have proven safe and effective. While many proof-of-concept studies in animal models of retinal disease have suggested that gene transfer to the neural retina will also be effective, a photoreceptor-targeting AAV vector has yet to be used in the clinic, principally because a vector that efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
114
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(121 citation statements)
references
References 68 publications
(108 reference statements)
5
114
2
Order By: Relevance
“…The only reports of AAV8-mediated photoreceptor expression in NHP indicated that AAV8 at (1 · 10 10 vg) did not efficiently transduce foveal, parafoveal, or perifoveal cones following subretinal injection (Vandenberghe et al, 2011a(Vandenberghe et al, 2011b. In contrast, AAV5 efficiently transduces cones in all these areas of NHP retina at comparable vector concentration (Boye et al, 2012). Hence, assuming a subretinal delivery route, the evidence to date would support the use of AAV5 in conjunction with the GRK1 promoter for driving GC1 expression in a clinical setting.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The only reports of AAV8-mediated photoreceptor expression in NHP indicated that AAV8 at (1 · 10 10 vg) did not efficiently transduce foveal, parafoveal, or perifoveal cones following subretinal injection (Vandenberghe et al, 2011a(Vandenberghe et al, 2011b. In contrast, AAV5 efficiently transduces cones in all these areas of NHP retina at comparable vector concentration (Boye et al, 2012). Hence, assuming a subretinal delivery route, the evidence to date would support the use of AAV5 in conjunction with the GRK1 promoter for driving GC1 expression in a clinical setting.…”
Section: Discussionmentioning
confidence: 97%
“…Multiple studies have shown that the human rhodopsin kinase (hGRK1) promoter drives efficient and rod/cone-specific transgene expression in mice (Khani et al, 2007;Boye et al, 2010Boye et al, , 2011Pawlyk et al, 2010;Sun et al, 2010;Mihelec et al, 2011) and most recently in nonhuman primates (Boye et al, 2012). Notably, within the NHP retina, the hGRK1 promoter was active in foveal cones (Boye et al, 2012). Viral serotype choice is dependent upon the route of administration as transduction profiles differ greatly depending on where the vector is deposited (Vandenberghe and Auricchio, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Mice were injected intravitreally with 4 ϫ 10 10 vg (high dose) or 4 ϫ 10 9 vg (low dose) or subretinally with 1 ϫ 10 10 vg (high dose) or 2 ϫ 10 9 vg (low dose). Although C57Bl/6J mice do not have sortable photoreceptors and, thus, FACS cannot be used as described above, hGRK1 has been shown to restrict transgene expression to rods and cones following subretinal injection (14,57). Representative fundus images and retinal cross sections revealed a clear dose response for each vector following either injection route (Fig.…”
Section: Aav2 Y-f and Y-f؉t-v Variants Bind Hs Aav2-based Variants Cmentioning
confidence: 95%
“…Data described above revealed that both AAV2(quadY-FϩT-V) and AAV2(4pMut) transduce rod photoreceptors following Ivt injection. We next quantified the relative performance of these variants by utilizing a construct containing the photoreceptor-specific human rhodopsin kinase (hGRK1) promoter driving mCherry in C57Bl/6J mice (14,57). Mice were injected intravitreally with 4 ϫ 10 10 vg (high dose) or 4 ϫ 10 9 vg (low dose) or subretinally with 1 ϫ 10 10 vg (high dose) or 2 ϫ 10 9 vg (low dose).…”
Section: Aav2 Y-f and Y-f؉t-v Variants Bind Hs Aav2-based Variants Cmentioning
confidence: 99%
See 1 more Smart Citation